2020
DOI: 10.21203/rs.3.rs-119151/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for rapid axial length elongation with low concentration atropine for myopia control

Abstract: Three hundred and twenty-eight myopic children, randomized to use either 0.01% (N=166) or 0.02% (N=162) atropine were enrolled in this study. Gender, age, body mass index(BMI), parental myopia status, atropine concentration used, pupil diameter, amplitude of accommodation, spherical equivalent refractive error (SER), anterior chamber depth (ACD) and axial length (AL) were collected at baseline and 1 year after using atropine. Rapid AL elongation was defined as >0.36 mm growth per year. Univariate analyses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Some studies 12,13,37 found that low-dose atropine controlled myopia progression and AL elongation synchronously. However, in the ATOM2 study, 41 the changes in AL and changes in SER were not synchronous, whereas the degree of myopia was stable, and AL continued to increase between 8 and 24 months after using 0.01% atropine. In this study, after 1 year of 0.01% atropine treatment, the changes in SER corresponded to the changes in AL.…”
Section: Discussionmentioning
confidence: 81%
“…Some studies 12,13,37 found that low-dose atropine controlled myopia progression and AL elongation synchronously. However, in the ATOM2 study, 41 the changes in AL and changes in SER were not synchronous, whereas the degree of myopia was stable, and AL continued to increase between 8 and 24 months after using 0.01% atropine. In this study, after 1 year of 0.01% atropine treatment, the changes in SER corresponded to the changes in AL.…”
Section: Discussionmentioning
confidence: 81%
“…Individual slope and intercept were included as random effects and an unstructured covariance matrix was used to control inter-subject variation. It was found that baseline age and SER were associated with axial elongation in children who underwent orthoky [14,36,37] or treatment of low-concentration atropine [38,39]. Thus, baseline age and SER were included as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in PD is one of the most important side effects of low-dose atropine eye drops [5][6][7]15]. Our study found that 0.01% atropine had a minimal impact on PD in the combination groups.…”
Section: Discussionmentioning
confidence: 47%
“…The details of the examination method for the observation items have been published elsewhere and are briefly described here [7,15]. AL, corneal power, and anterior chamber depth (ACD) were evaluated using a non-contact partial coherence interferometer (IOLMaster; Carl Zeiss Meditec AG, Germany).…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation